2021
DOI: 10.1002/bse.2801
|View full text |Cite
|
Sign up to set email alerts
|

Enabling the Circular Economy transition: a sustainable lean manufacturing recipe for Industry 4.0

Abstract: Over the past 10 years, the concepts and objectives of circular economy have been increasingly detailed and become strategic issues of international, European, and national policies. However, the transition towards circular production models continues to be affected by several barriers and critical factors that make the transition difficult to achieve. The paper tries to design a relationship between sustainable production and lean production, highlighting the opportunity to invest in reverse‐logistics and how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(121 citation statements)
references
References 91 publications
2
79
0
2
Order By: Relevance
“…Moreover, the implication of Industry 4.0 and digital technologies for the circular economy has received considerable attention (Gupta et al, 2021; Nascimento et al, 2019). For example, Ciliberto et al (2021) identified and explained the correlations among various features of circular economy and Industry 4.0. Alternatively, Awan et al (2021) offered a deep understanding of business and sociopolitical interests and expectations regarding circular economy transition under the Industry 4.0 context.…”
Section: Industry 40 and Sustainable Innovationmentioning
confidence: 99%
“…Moreover, the implication of Industry 4.0 and digital technologies for the circular economy has received considerable attention (Gupta et al, 2021; Nascimento et al, 2019). For example, Ciliberto et al (2021) identified and explained the correlations among various features of circular economy and Industry 4.0. Alternatively, Awan et al (2021) offered a deep understanding of business and sociopolitical interests and expectations regarding circular economy transition under the Industry 4.0 context.…”
Section: Industry 40 and Sustainable Innovationmentioning
confidence: 99%
“…The circular economy is a well-rooted concept in the area of sustainable development (Geissdoerfer et al, 2017;Kirchherr et al, 2017;Schroeder et al, 2019;Horvath et al, 2019;Stankevičienė & Nikanorova, 2020), waste management (Ji et al, 2018), part of the intellectual concept of the green economy (D' Amato et al, 2017), as well as supply chain (Braz et al, 2018) were heavily discussed within public policy, as well as at the level of organization and business models (Michelini et al, 2017). CE is also associated with the model of industrial symbiosis, which assumes vital business networking to create values and competitive advantages (Yazan & Fraccascia, 2019), and industry 4.0 (Khan et al, 2021;Rajput & Singh, 2020;Ciliberto et al, 2021). CE is also recognized as an evolving approach aiming at the sustainable usage of various raw materials and natural resources (McDowall et al, 2017), requiring a move from the traditional approach or linear model of "take, make, use and dispose/waste" to the innovative approach based on circular model of "reduce, reuse, recycle, recover, remanufacture and redesign" (Jabbour et al, 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Collaborative efforts, knowledge sharing in sustainability management and marketisation of the waste recycling represent the actions that need to be performed to adopt circular economy (Saha et al, 2020). Smart technologies and digital environment could improve the potential of the manufacturing supply chain but there is need for greater awareness of the enhanced paradigms in interactions between human and machine (Ciliberto et al, 2021). In article (García‐Quevedo et al, 2020) has been stressed out there is lack of human resources as an obstacle by firm engaged in circular economy activities.…”
Section: Introductionmentioning
confidence: 99%
“…Smart technologies and digital environment could improve the potential of the manufacturing supply chain but there is need for greater awareness of the enhanced paradigms in interactions between human and machine (Ciliberto et al, 2021). In article (García-Quevedo et al, 2020) has been stressed out there is lack of human resources as an obstacle by firm engaged in circular economy activities.…”
mentioning
confidence: 99%